Arms and the people popular movements and the military from the Paris Commune to the Arab Spring - Gonzalez, Mike; Barekat, Houman (Pluto Press, 2013)
Looking at a range of global historical experiences, Arms and the People examines the relationship between mass movements and military institutions. With a range of international contributors who have either studied or been directly involved in such social upheavals, Arms and the People is a pioneering contribution to the study of revolutionary change and will appeal to students and academics in history, politics and sociology.